Analyzing The Contemporary Developments and Challenges in Teaching English Language in Pakistani Schools - Shafique, Ayesha; Amjad, Azka; Khurshid, Nimra; Bin Zubair, Hassan (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
English phraseology is a required subject taught at the Pakistan graduate level. Even after surveying the English terminology for over 14 years, the plurality of learners arriving from non-elite organizations, need the basic grip in English language skills to maintain their elevated schooling and proficient fields. With this reasoning, the recent investigation concentrated on developing English composition and assignment techniques, and in Karachi private non-elite organizations confronted the difficulties while developing these techniques at the SSC (Secondary School Certificate) level. Qualitative as well as quantitative method has been used. The variety of the investigation included 20 SSC level students, 12 SSC level English language teachers of non-elite private schools, and 5 student notebooks. Characteristics were composed through open-ended votes, committees’ consultations, and tablet examination. Data were examined adopting subjective analysis. The conclusions disclosed that developing English language assignment strategies involve reading the passage aloud, paraphrasing the passage, furnishing the basic suggestion and significance of tough phrases to the students. The prominent difficulties struggled by the instructors in instructing reading skills are learners’ absence of attention in reading, absence of pursuit, and soft reading cognition skills. The investigation also indicated methods of teaching writing skills such as the requirement of standard texts and appropriate terminology sections. The main dilemmas while developing writing skills include a shortage of pre-writing recreations, beginners’ deficient grip over vocabulary, punctuation, grammar, and spelling, voluble syllabus, and restricted time.